Spatial Mapping of Healthcare-Associated Infections (HAIs) Risks Based on Sanitation Facility Availability and Patient Density Ratios in Hospitals Across Indonesia - Sari, Mila (CV. Get Press Indonesia, 2026)
Patient safety regarding the persistent threat of Healthcare-Associated Infections (HAIs) remains a critical challenge in Indonesia, driven by significant infrastructural disparities and operational strains. This study aims to map the national geospatial risk of HAIs by testing the hypothesis that the intersection between sanitation limitations and patient density creates distinct regional risk clusters. Adopting a quantitative descriptive design with retrospective spatial analysis, the research examines secondary data from 3,155 hospitals across 38 provinces, sourced from Siranap, RS Online, and the Indonesian Health Profile for the 2022-2024 period. Key variables, including handwashing station availability, potable water access, and Bed Occupancy Rate (BOR), were integrated using Spatial Join techniques. The results reveal a